Are emergency care departments too noisy? - Ghadah Alghbewi; Faten Khayat; Nejood Alsheikh; Abdulmajid Asiri; Mohammad Alsaif; Reem Alsalamah; Majid Alsalamah (Saudi Journal of Emergency Medicine)
Background: Noise pollution is a serious issue that faces healthcare centers. It is associated with detrimental effects on both the patient's and the healthcare provider's mental and physical well-being. It could also negatively impact the physician's decision-making. Aim: There are no similar studies conducted in the past 5 years in Saudi Arabia. This is the first study to measure noise levels and deem them pollutants in an emergency care center in Saudi Arabia. Method: This cross-sectional study was conducted in the emergency department (ED) of a tertiary care hospital to assess the level of noise pollution. Noise levels were evaluated in the ED by using a calibrated decibel meter device in three selected units including resuscitation, acute care, and pediatrics unit. Noise levels were only measured during weekdays. In each unit, readings were obtained over 24 hours. Results: Over 24 hours, measurements of all assessed units showed that noise levels exceeded WHO guidelines for hospitals, which recommend sound levels below 40 decibels (dB). Among all clinical areas, the pediatric unit exhibited the highest noise spike (97.3 dB), followed by the resuscitation unit (88.5 dB), and the acute care unit (87.3 dB). Conclusion: Noise levels were high in all the assessed units, which places the patient's well-being and recovery at risk. Moreover, high noise levels could contribute to adverse outcomes for the healthcare provider. More studies should focus on assessing the noise levels in other departments and the efficacy of different intervention methods. [SJEMed 2023; 4(2.000): 087-091]